Biomedical sample transportation in the province of Quebec: a case study. Issue 2 (17th January 2016) - Anaya-Arenas, Ana Maria; Chabot, Thomas; Renaud, Jacques; Ruiz, Angel
Abstract : Biomedical sample management plays a central role in an efficient health care system and requires important resources. Based on our collaboration with the Quebec's Ministère de la Santé et des Services sociaux (Ministry of Health and Social Services), this article describes the challenging context of biomedical sample transportation in the Canadian province of Quebec. It is modelled on a variant of the multi-trip vehicle routing problem with time windows where routes need to be planned from a laboratory to satisfy the multiple pick-up requests of each sample collection centre under some practical constraints. We propose and evaluate two alternative mathematical formulations, as well as fast heuristics, to minimise total transportation distances. The performance of the proposed methods is assessed over a large case study based on the network of laboratories in the province of Quebec.